The organisation of the criminal justice in French West Africa : the case of Senegal of 1887 at the dawn of independances (1887-1960) - (:unkn) unknown (My University, 2017)
The period going from 1887 to the independences (1960) allows us to approach the question of the justice in French West Africa by highlighting the transformation of rules and the exercise of the justice, as well as the meeting between the Western system and the local legal pluralism. In Senegal as in the other territories of the French West Africa, the legal and judicial evolution reveals the opposition between two trends: that of the assimilation and that of the adaptation. Within the framework of this confrontation, jurisdictions that are unknown in the mainland France are created in the colonies in order to remedy with the lack of staff and with the financial means of the jurisdictions. For these same reasons the collegiality remains very rare and the justice is often organized around only one judge who is in charge of the pursuit, the investigation and the judgement. The organisation of the native penal justice set up in 1903, practically meets with the will of keeping the native institutions. However, the desire of assimilation leads to achieve around it reforms which tend to weaken the native institutions.
Keywords: African Research